Process of strategic management at Surabaya City government in achieving Green City Master Plan (GCMP) - Aditya, Bayu Rizky (Jurnal Ilmiah Administrasi Publik, 2016)
This study aims to show the strategic management process of Surabaya City Government in achieving Green City Master Plan (GCMP), especially from the beginning to the end of process. This study analyzed the strategic management process of Surabaya City Government by using qualitative research with an interview to key informants in Surabaya Development Planning Board and analyze Surabaya Development Planning Documents. The result showed that the process is conducted through environmental scanning, formulation, implementation, control and evaluation process which is carried out continuously. The utilization of IT and social media as a liaison between the government and society, allowed the government to create an appropriate program which is supported by the society. The process that has been passed by Surabaya City Government is supposed to be a pilot project for other similar areas to be more effective in achievement of GCMP.